Pantun Dakwah Dalam Internet - Nor Adlyizan Theis; Tun Adam Khairell Tun Mazukie; Muhammad Danish Abqari Syamsul Faizi; Muhammad Amar Mirza Jasni; Muhammad Firzan Adriean Mohd Faizal (Kolej PERMATA Insan, 2025)
5th Insan Junior Researchers International Conference 2024 (iJURECON 2024) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Ahmad Bazli Ahmad Hilmi, Nurhidaya Mohamad Jan, Norazlina Subani 25-26 October 2024 Organized by : Kolej Permata Insan